Preparation method and application of N and S co-doped Fe-based electrocatalyst
The preparation of N and S co-doped Fe-based electrocatalysts through two-step calcination method, which solves the problem of uncertain distance control between heteroatoms and metal activity centers, and achieves excellent catalytic activity and stability for ORR and OER reactions, which is suitable for industrialization Production and display high performance in zinc air batteries.
Patent Information
- Application Number
- CN202411327477.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-23
- Publication Date
- 2024-12-27
AI Technical Summary
The prior art cannot effectively control the distance between the heteroatom and the metal active center, resulting in uncertain electronic regulation methods of oxygen reduction reaction (ORR) and oxygen precipitation reaction (OER) catalysts, affecting catalytic performance and stability.
The N and S-co-doped Fe-based electrocatalyst is prepared by using a two-step roasting method. By mixing sulfur source, carbon support and iron source in a specific proportion and roasting in an inert atmosphere, a highly conductive NC material is formed, and S atoms are accurately controlled. The electronic regulation method with Fe species forms Fe-S bond or remote electronic regulation.
Excellent electrocatalytic activity and stability for ORR and OER reactions are achieved, the cost of the catalyst is reduced, and it is suitable for industrial production, and the catalyst exhibits high open circuit voltage and peak power density for zinc-air batteries.
Smart Images

Figure CN119208632A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of non-precious metal electrocatalysts; more specifically, to a preparation method and application of a N and S co-doped Fe-based electrocatalyst. Background Art
[0002] With the global pursuit of alternatives to non-renewable energy sources such as fossil petroleum, clean and sustainable energy conversion devices such as fuel cells and metal-air batteries have attracted much attention. However, the performance of these energy conversion devices is severely affected by the sluggish kinetics of oxygen reduction reaction (ORR) and oxygen evolution reaction (OER). Therefore, the development of high-performance ORR and OER catalysts is crucial.
[0003] At present, platinum-based catalysts, ruthenium oxide, and iridium oxide using precious metals are still the ORR and OER catalysts with the most promising commercial applications. However, the high cost and scarce reserves of precious metals have led to the fact that most of the cost of commercial batteries is concentrated on precious metal catalysts, which seriously affects the commercial development of batteries. Therefore, it has become urgent to turn to the research of low-cost and high-natural abundance non-precious metal catalysts.
[0004] The catalytic performance and stability of non-precious metal catalysts still need to be improved. Electronic regulation of metal sites by heteroatoms is one of the effective strategies to improve ORR and OER performance. In this strategy, heteroatoms such as boron (B), phosphorus (P), and sulfur (S) are introduced into the catalyst to adjust the electronic structure of the metal site, thereby optimizing the oxygen reduction catalytic performance. Different microscopic distances between heteroatoms and metal species will cause different modification effects. For example, the close distance between heteroatoms and metal species can directly form chemical bonds and directly regulate the electrons to improve the catalytic activity, while the long distance between heteroatoms and metal species will change the local environment of the material surface, or the remote electronic regulation of heteroatoms on metal active centers will improve the catalytic activity of the catalyst.
[0005] However, the existing technology cannot effectively control the distance between heteroatoms and metal active centers, resulting in the inability to accurately control the electronic regulation of heteroatoms on metal active centers, which needs to be improved. Summary of the invention
[0006] In view of the shortcomings of the prior art, the first aspect of the present invention provides a method for preparing a N and S co-doped Fe-based electrocatalyst. The preparation method can accurately control the electronic regulation mode of S on Fe species by two-step calcination of a mixture precursor containing a specific sulfur source.
[0007] The preparation method of the N and S co-doped Fe-based electrocatalyst disclosed in the first aspect of the present invention comprises the following steps:
[0008] S1, mixing a sulfur source, a carbon support, dicyandiamide and an iron source uniformly to obtain a mixture precursor;
[0009] S2, calcining the mixture precursor under an inert atmosphere, first heating the mixture to 500-600° C. and keeping the temperature for 2 hours, then heating the mixture to 700-900° C. and keeping the temperature for 2 hours, to obtain a N and S co-doped Fe-based electrocatalyst;
[0010] Wherein, the sulfur source is L-cysteine or thiourea.
[0011] Furthermore, the above step S1 includes:
[0012] S11, uniformly mixing a sulfur source, a carbon carrier and dicyandiamide according to a predetermined ratio;
[0013] S12, adding an iron source to the mixture obtained in step S11, and mixing evenly to obtain the mixture precursor.
[0014] Furthermore, in step S11, the sulfur source, the carbon carrier and the dicyandiamide are uniformly mixed by a grinding method, and ethanol is added as a dispersant during the grinding process.
[0015] Furthermore, in step S12, ferric nitrate as the iron source is first dissolved in ethanol, and then the ethanol solution of ferric nitrate is added to the mixture obtained in step S11 and ground and mixed to improve the dispersion uniformity of Fe in the mixture precursor.
[0016] Furthermore, in step S11, the sulfur source, the carbon carrier and dicyandiamide are mixed in a mass ratio of 7 to 25:5:200.
[0017] Furthermore, in step S1, the mass ratio of the iron source to the carbon carrier is 1.5-2.5:5.
[0018] Furthermore, the carbon carrier is carbon black.
[0019] Furthermore, in step S2, the temperature is first increased to 550°C at a heating rate of 2°C / min to 3°C / min and kept at this temperature for 2 hours, and then increased to 800°C at a heating rate of 3°C / min to 6°C / min and kept at this temperature for 2 hours.
[0020] The second aspect of the present invention discloses the application of the N, S co-doped Fe-based electrocatalyst obtained by the above preparation method in ORR and OER reactions.
[0021] The technical solution of the present invention has the following beneficial effects:
[0022] In the present invention, a mixture precursor including L-cysteine / thiourea, a carbon carrier, dicyandiamide and an iron source is subjected to two-step calcination to obtain a N and S co-doped Fe-based electrocatalyst. The synthesis process is simple and low in cost, and is suitable for industrial production.
[0023] During the calcination / pyrolysis process, the mixture precursor forms a highly conductive NC material g-C3N4, and g-C3N4 has a strong anchoring ability, which can evenly disperse the metal Fe to prevent it from agglomerating; at the same time, during the calcination / pyrolysis process, L-cysteine and thiourea can form a certain interaction relationship with Fe species to accurately control the electronic regulation mode of S atoms and Fe species: when L-cysteine is used as a sulfur source, S and Fe will directly form Fe-S bonds, allowing S atoms to directly regulate the electronic regulation of Fe species, while when thiourea is used as a sulfur source, S and Fe do not form Fe-S bonds, allowing S atoms to remotely regulate the electronic regulation of Fe species. After the second step of calcination at a higher temperature, the specific electronic regulation state of S on Fe species is retained, and finally a N, S co-doped Fe-based electrocatalyst with a specific regulation mode is formed, and the catalyst has excellent electrocatalytic activity and stability for both ORR and OER reactions.
[0024] In order to more clearly illustrate the purpose, technical solutions and advantages of the present invention, the present invention is further described in detail below in conjunction with the accompanying drawings and specific implementation methods. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 is an exemplary flow chart of an embodiment of a method for preparing a catalyst according to the present invention;
[0026] Figure 2 The Fe / S prepared in Example 1, Example 2 and Comparative Example 1 L NC, Fe / S T XRD characterization patterns of NC and Fe / NC catalysts;
[0027] Figure 3 The Fe / S prepared in Example 1 and Example 2 L NC and Fe / S T SEM image of NC catalyst;
[0028] Figure 4 The Fe / S prepared in Example 1 L TEM image of NC catalyst;
[0029] Figure 5 The Fe / S prepared in Example 2 T TEM image of NC catalyst;
[0030] Figure 6 The Fe / S prepared in Example 1 LXPS pattern of NC catalyst S2p;
[0031] Figure 7 The Fe / S prepared in Example 2 T XPS pattern of NC catalyst S2p;
[0032] Figure 8 The Fe / S prepared in the examples and comparative examples L NC catalyst, Fe / S T Comparison of linear sweep voltammetry (LSV) curves of ORR of NC catalyst, Fe / NC catalyst, and NC catalyst;
[0033] Fig. 9 The Fe / S prepared in the examples and comparative examples L NC catalyst, Fe / S T Tafel slope fitting curves of NC catalyst, Fe / NC catalyst, and NC catalyst;
[0034] Fig.10 The Fe / S prepared in the examples and comparative examples L NC catalyst, Fe / S T Comparison of linear sweep voltammetry (LSV) curves of OER of NC catalyst and Fe / NC catalyst;
[0035] Fig.11 The Fe / S prepared in the examples and comparative examples L NC catalyst, Fe / S T Comparison of the OER impedance (EIS) of NC catalyst and Fe / NC catalyst;
[0036] Fig.12 The Fe / S prepared in Example 1 L Open circuit voltage test diagram of zinc-air battery with NC catalyst and commercial Pt / C+RuO2;
[0037] Fig.13 The Fe / S prepared in Example 1 L Peak power density test diagram of zinc-air battery with NC catalyst and commercial Pt / C+RuO2;
[0038] Fig.14 is a comparison chart of ORR LSV of the catalysts prepared in Examples 1, 3 and 5;
[0039] Fig.15 is a comparison chart of ORR LSV of the catalysts prepared in Examples 2, 4 and 6;
[0040] Fig.16 This is a comparison chart of the ORR LSV of the catalysts prepared in Comparative Examples 1, 3 and 4. DETAILED DESCRIPTION
[0041] like Figure 1 As shown, the preparation method of the N and S co-doped Fe-based catalyst in the embodiment of the present invention comprises the following steps:
[0042] (1) Dissolve 0.05mmol of ferric nitrate nonahydrate in 10ml of anhydrous ethanol and perform ultrasonic dispersion. The ultrasonic dispersion time can be 2 to 10min.
[0043] (2) L-cysteine or thiourea as a sulfur source, ultra-high conductive carbon black BP2000 and dicyandiamide are placed in a mortar, and an appropriate amount (e.g., 2 ml) of ethanol is added as a co-solvent and dispersant, and then mixed and ground evenly to obtain a dark gray solid mixture; wherein the sulfur source, carbon black BP2000 and dicyandiamide can be added in a mass ratio of X:5:200 (wherein the range of X is 7 to 25);
[0044] ⑶ Add the ethanol solution of iron nitrate to the mixture obtained in step ⑵ and grind thoroughly until the ethanol solution is completely added to obtain a black mixture precursor;
[0045] (4) The mixture precursor obtained in the previous step is placed in a tube furnace and calcined under an inert atmosphere (such as nitrogen) to obtain a catalyst Fe / S L NC or Fe / S T NC.
[0046] The calcination temperature program is to heat the temperature to 500-600°C (for example, 550°C) at a heating rate of 2°C / min-3°C / min (for example, 2.5°C / min) and keep it warm for 1-3 hours (for example, 2 hours); then heat the temperature to 700-900°C (for example, 550°C) at a heating rate of 3°C / min-6°C / min (for example, 5°C / min) and keep it warm for 1-3 hours (for example, 2 hours).
[0047] The Fe / S L NC or Fe / S T The main phase of Fe in NC catalyst is Fe nanoparticles. L In the NC catalyst, S forms Fe-S bonds with Fe species for direct electronic regulation, while Fe / S using thiourea as the sulfur source T In the NC catalyst, S and Fe species are not bonded to perform remote electronic regulation.
[0048] Hereinafter, the present invention is described in more detail based on specific examples and comparative examples.
[0049] Example 1Fe / S L Preparation of NC catalyst
[0050] Ferric nitrate nonahydrate (0.05 mmol, 20.2 mg) was added to 10 ml of anhydrous ethanol and ultrasonicated for 2 min;
[0051] L-cysteine (1.5 mmol, 181.7 mg), ultrahigh conductive carbon black BP2000 (50 mg) and dicyandiamide (2 g) were placed in a mortar, 2 mL of ethanol was added as a cosolvent and dispersant, and ground for 10 min to obtain a dark gray solid mixture;
[0052] Slowly drop an ethanol solution of ferric nitrate nonahydrate into the above mixture, and grind thoroughly until the ethanol solution is completely added, and continue grinding to obtain a black mixture precursor;
[0053] The mixture precursor obtained in the previous step was placed in a tubular atmosphere furnace, heated to 550°C at a heating rate of 2.5°C / min under a nitrogen atmosphere, kept at this temperature for 2 hours, and then heated to 800°C at a heating rate of 5°C / min and kept at this temperature for 2 hours to obtain the catalyst Fe / S L NC.
[0054] Example 2Fe / S T Preparation of NC catalyst
[0055] Ferric nitrate nonahydrate (0.05 mmol, 20.2 mg) was added to 10 ml of anhydrous ethanol and ultrasonicated for 2 min;
[0056] Thiourea (1.5 mmol, 114.2 mg), ultrahigh conductive carbon black BP2000 (50 mg) and dicyandiamide (2 g) were placed in a mortar, 2 mL of ethanol was added as a cosolvent and dispersant, and ground for 10 min to obtain a dark gray solid mixture;
[0057] Slowly drop an ethanol solution of ferric nitrate nonahydrate into the above mixture, and grind thoroughly until the ethanol solution is completely added, and continue grinding to obtain a black mixture precursor;
[0058] The mixture precursor obtained in the previous step was placed in a tubular atmosphere furnace, heated to 550°C at a heating rate of 2.5°C / min under a nitrogen atmosphere, kept at this temperature for 2 hours, and then heated to 800°C at a heating rate of 5°C / min and kept at this temperature for 2 hours to obtain the catalyst Fe / S T NC.
[0059] Example 3Fe / S 1.0L Preparation of NC catalyst
[0060] Ferric nitrate nonahydrate (0.05 mmol, 20.2 mg) was added to 10 ml of anhydrous ethanol and ultrasonicated for 2 min;
[0061] L-cysteine (1.0 mmol, 121.2 mg), ultrahigh conductive carbon black BP2000 (50 mg) and dicyandiamide (2 g) were placed in a mortar, 2 mL of ethanol was added as a cosolvent and dispersant, and ground for 10 min to obtain a dark gray solid mixture;
[0062] Slowly drop an ethanol solution of ferric nitrate nonahydrate into the above mixture, and grind thoroughly until the ethanol solution is completely added, and continue grinding to obtain a black mixture precursor;
[0063] The mixture precursor obtained in the previous step was placed in a tubular atmosphere furnace, heated to 550°C at a heating rate of 2.5°C under a nitrogen atmosphere, kept at this temperature for 2 hours, and then heated to 800°C at a heating rate of 5°C / min and kept at this temperature for 2 hours to obtain the catalyst Fe / S 1.0L NC.
[0064] Example 4Fe / S 1.0T Preparation of NC catalyst
[0065] Ferric nitrate nonahydrate (0.05 mmol, 20.2 mg) was added to 10 ml of anhydrous ethanol and ultrasonicated for 2 min;
[0066] Thiourea (1.0 mmol, 76.1 mg), ultrahigh conductive carbon black BP2000 (50 mg) and dicyandiamide (2 g) were placed in a mortar, 2 mL of ethanol was added as a cosolvent and dispersant, and ground for 10 min to obtain a dark gray solid mixture;
[0067] Slowly drop an ethanol solution of ferric nitrate nonahydrate into the above mixture, and grind thoroughly until the ethanol solution is completely added, and continue grinding to obtain a black mixture precursor;
[0068] The mixture precursor obtained in the previous step was placed in a tubular atmosphere furnace, heated to 550°C at a heating rate of 2.5°C / min under a nitrogen atmosphere, kept at this temperature for 2 hours, and then heated to 800°C at a heating rate of 5°C / min and kept at this temperature for 2 hours to obtain the catalyst Fe / S 1.0T NC.
[0069] Example 5Fe / S 2.0L Preparation of NC catalyst
[0070] Ferric nitrate nonahydrate (0.05 mmol, 20.2 mg) was added to 10 ml of anhydrous ethanol and ultrasonicated for 2 min;
[0071] L-cysteine (2.0 mmol, 242.3 mg), ultrahigh conductive carbon black BP2000 (50 mg) and dicyandiamide (2 g) were placed in a mortar, 2 mL of ethanol was added as a cosolvent and dispersant, and ground for 10 min to obtain a dark gray solid mixture;
[0072] Slowly drop an ethanol solution of ferric nitrate nonahydrate into the above mixture, and grind thoroughly until the ethanol solution is completely added, and continue grinding to obtain a black mixture precursor;
[0073] The mixture precursor obtained in the previous step was placed in a tubular atmosphere furnace, heated to 550°C at a heating rate of 2.5°C / min under a nitrogen atmosphere, kept at this temperature for 2 hours, and then heated to 800°C at a heating rate of 5°C / min and kept at this temperature for 2 hours to obtain the catalyst Fe / S 2.0L NC.
[0074] Example 6Fe / S 2.0T Preparation of NC catalyst
[0075] Ferric nitrate nonahydrate (0.05 mmol, 20.2 mg) was added to 10 ml of anhydrous ethanol and ultrasonicated for 2 min;
[0076] Thiourea (2.0 mmol, 152.2 mg), ultrahigh conductive carbon black BP2000 (50 mg) and dicyandiamide (2 g) were placed in a mortar, 2 mL of ethanol was added as a cosolvent and dispersant, and ground for 10 min to obtain a dark gray solid mixture;
[0077] Slowly drop an ethanol solution of ferric nitrate nonahydrate into the above mixture, and grind thoroughly until the ethanol solution is completely added, and continue grinding to obtain a black mixture precursor;
[0078] The mixture precursor obtained in the previous step was placed in a tubular atmosphere furnace, heated to 550°C at a heating rate of 2.5°C / min under a nitrogen atmosphere, kept at this temperature for 2 hours, and then heated to 800°C at a heating rate of 5°C / min and kept at this temperature for 2 hours to obtain the catalyst Fe / S 2.0T NC.
[0079] Comparative Example 1 Preparation of Fe / NC Catalyst
[0080] The difference between Comparative Example 1 and the embodiment is that no S source is added, and the specific steps are as follows:
[0081] Ferric nitrate nonahydrate (0.05 mmol, 20.2 mg) was added to 10 ml of anhydrous ethanol and ultrasonicated for 2 min;
[0082] Ultrahigh conductive carbon black BP2000 (50 mg) and dicyandiamide (2 g) were placed in a mortar, 2 mL of ethanol was added as a cosolvent and dispersant, and ground for 10 min to obtain a dark gray solid mixture;
[0083] Slowly adding an ethanol solution of ferric nitrate nonahydrate to the above mixture, and grinding thoroughly until the ethanol solution is completely added, and continuing grinding to obtain a mixture precursor;
[0084] The mixture precursor obtained in the previous step was placed in a tubular atmosphere furnace, heated to 550°C at a heating rate of 2.5°C / min under a nitrogen atmosphere, kept warm for 2 hours, then heated to 800°C at a heating rate of 5°C / min, and kept warm for 2 hours to obtain the catalyst Fe / NC.
[0085] Comparative Example 2 Preparation of NC Catalyst
[0086] The difference between Comparative Example 2 and the embodiment is that no Fe source and S source are used, and the specific steps are as follows:
[0087] Ultrahigh conductive carbon black BP2000 (50 mg) and dicyandiamide (2 g) were placed in a mortar, 2 mL of ethanol was added as a cosolvent and dispersant, and ground for 10 min to obtain a dark gray solid mixture;
[0088] The mixture obtained in the previous step was placed in a tubular atmosphere furnace, heated to 550°C at a heating rate of 2.5°C / min under a nitrogen atmosphere, kept warm for 2 hours, and then heated to 800°C at a heating rate of 5°C / min and kept warm for 2 hours to obtain catalyst NC.
[0089] Comparative Example 3 Preparation of Fe / NC-700 Catalyst
[0090] The difference between Comparative Example 3 and Comparative Example 1 is that the carbonization temperature is different, and the specific steps are as follows:
[0091] Ferric nitrate nonahydrate (0.05 mmol, 20.2 mg) was added to 10 ml of anhydrous ethanol and ultrasonicated for 2 min;
[0092] Ultrahigh conductive carbon black BP2000 (50 mg) and dicyandiamide (2 g) were placed in a mortar, 2 mL of ethanol was added as a cosolvent and dispersant, and ground for 10 min to obtain a dark gray solid mixture;
[0093] Slowly drop an ethanol solution of ferric nitrate nonahydrate into the above mixture, and grind thoroughly until the ethanol solution is completely added, and continue grinding to obtain a precursor mixture;
[0094] The mixture obtained in the previous step was placed in a tubular atmosphere furnace, heated to 550°C at a heating rate of 2.5°C / min under a nitrogen atmosphere, kept warm for 2 hours, and then heated to 700°C at a heating rate of 5°C / min and kept warm for 2 hours to obtain the catalyst Fe / NC-700.
[0095] Comparative Example 4 Preparation of Fe / NC-900 Catalyst
[0096] The difference between Comparative Example 4 and Comparative Example 1 is that the carbonization temperature is different, and the specific steps are as follows:
[0097] Ferric nitrate nonahydrate (0.05 mmol, 20.2 mg) was added to 10 ml of anhydrous ethanol and ultrasonicated for 2 min;
[0098] Ultrahigh conductive carbon black BP2000 (50 mg) and dicyandiamide (2 g) were placed in a mortar, 2 mL of ethanol was added as a cosolvent and dispersant, and ground for 10 min to obtain a dark gray solid mixture;
[0099] Slowly drop an ethanol solution of ferric nitrate nonahydrate into the above mixture, and grind thoroughly until the solution is completely added, and continue grinding to obtain a mixture precursor;
[0100] The mixture precursor obtained in the previous step was placed in a tubular atmosphere furnace, heated to 550°C at a heating rate of 2.5°C / min under a nitrogen atmosphere, kept warm for 2 hours, and then heated to 900°C at a heating rate of 5°C / min and kept warm for 2 hours to obtain the catalyst Fe / NC-900.
[0101] Phase and morphology analysis of examples and comparative examples
[0102] Figure 2 The Fe / S prepared in Example 1, Example 2 and Comparative Example 1 L NC, Fe / S T By comparing the XRD patterns of NC and Fe / NC catalysts with the PDF cards, we can see that the Fe phase in the catalyst is basically single substance Fe, specifically in the form of BCC Fe and FCCFe. By comparing the diffraction peaks, we find that the particle size of single substance Fe gradually increases. Figure 3 a and b are respectively Fe / S in Example 1 L NC catalyst and Fe / S in Example 2 T From the FE-SEM images of the NC catalyst, it can be seen that the structures of both catalysts are granular and retain the morphology of BP2000.
[0103] Figure 4 The Fe / S prepared in Example 1 L TEM image of NC catalyst. It can be seen from the image that the metal Fe nanoparticles in the catalyst are extremely small and can only be observed under high-resolution TEM. Figure 5 TEM image of the catalyst Fe / STNC prepared in Example 2. It can be observed from the image that the size of the metal Fe nanoparticles is larger than that in Example 1, which is consistent with Figure 2 The results correspond.
[0104] Figure 6 The Fe / S prepared in Example 1 LFrom the XPS graph of S2p of the NC catalyst, it can be clearly observed that the metal Fe and S atoms formed Fe-S bonds, indicating that the S atoms directly regulated the electrons of the Fe species. Figure 7 The Fe / S prepared in Example 2 T From the XPS graph of S2p of the NC catalyst, it can be observed that the metal Fe and S atoms do not form a direct bond, but the S atoms loaded on the carbon skeleton indirectly act on the Fe species, indicating that the S atoms perform remote electronic regulation on the Fe species. It can be seen that during the calcination / pyrolysis process, both L-cysteine and thiourea can form a certain interaction relationship with the Fe species to accurately control the electronic regulation mode of the S atoms and the Fe species.
[0105] Catalytic Performance Test of Examples
[0106] ORR test conditions: The test was carried out using a rotating disk electrode with a rotation speed of 1600 rpm and a catalyst loading of 0.6 mg cm -2 , tested using a three-electrode system in an O2-saturated 0.1 mol / L KOH solution; the reference electrode was an Ag / AgCl electrode and the counter electrode was a platinum electrode.
[0107] OER test conditions: The working electrode was prepared by dropping the catalyst ink onto a 1×1 cm nickel foam with a catalyst loading of 1 mg cm -2 , tested in 1.0 mol / L KOH solution using a three-electrode system; wherein the reference electrode was an Ag / AgCl electrode and the counter electrode was a platinum electrode.
[0108] Zinc-air battery test: zinc sheet as anode, loaded with 0.6 mg cm -2 The carbon paper with catalyst was used as air cathode, and the electrolyte was a mixture of 6.0 mol / L KOH and 0.2 mol / L ZnAc.
[0109] All potentials are converted to standard hydrogen electrode potentials.
[0110] Figure 8 Example 1 (Fe / S L NC), Example 2 (Fe / S T NC), Comparative Example 1 (Fe / NC) and Comparative Example 2 (NC) ORR linear sweep voltammetry (LSV) curve comparison diagram of the catalysts in the figure. The starting potential and half-wave potential data of each catalyst are specifically shown in Table 1 below.
[0111] Table 1: Test data of starting potential and half-wave potential of ORR reaction of catalyst
[0112] Starting potential Half-wave potential Example 1 1.06V 0.89V Example 2 0.98V 0.84V Comparative Example 1 0.98V 0.83V Comparative Example 2 0.91V 0.79V
[0113] Fig. 9 The Tafel slope curves of the catalysts in Example 1, Example 2, Comparative Example 1 and Comparative Example 2 are shown in Table 1. The Tafel slope curves of the catalysts in Example 1 and Example 2 are significantly lower than those in Comparative Example 1 and Comparative Example 2. L The NC catalyst exhibits the smallest slope, indicating that its ORR catalytic reaction rate is the fastest.
[0114] Combination Figure 8 and Fig. 9 It can be seen that both the remote electronic regulation and direct electronic regulation of S atoms on Fe species can improve the ORR catalytic performance of the catalyst; and the Fe / S L NC catalyst is superior to Fe / S in Example 2 T NC catalyst exhibits the best ORR reaction activity, indicating that the direct electronic regulation of S atoms on Fe species has a more significant effect in improving ORR activity.
[0115] Fig.10 1 is a comparison diagram of the OER linear sweep voltammetry (LSV) curves of the catalysts in Example 1, Example 2 and Comparative Example 1. Fig.10 It can be seen intuitively that the Fe / S L NC catalyst and Fe / S of Example 2 T NC catalyst at 50 mA cm -2 The potential at the current density is 1.58 V and 1.62 V, which is significantly better than 1.66 V of the Fe / NC catalyst prepared in Comparative Example 1, indicating that the addition of S atoms, whether direct electronic regulation or remote electronic regulation, can make the catalyst exhibit better OER performance, and the OER performance under direct electronic regulation is better than that under remote electronic regulation.
[0116] Fig.11 The Fe / S prepared in Example 1, Example 2 and Comparative Example 1 L NC catalyst, Fe / S T EIS impedance diagram of NC catalyst and Fe / NC catalyst. It can be seen from the figure that Fe / S L The electrochemical impedance of NC is the smallest, and it has the best mass transfer and conductivity.
[0117] Based on the above electrochemical tests, Fe / S L NC showed the best electrochemical performance and was assembled into a zinc-air battery for testing.
[0118] Fig.12 The Fe / S prepared in Example 1 LThe open circuit voltage test diagram of zinc-air battery of NC catalyst and commercial Pt / C+RuO2. Compared with commercial Pt / C+RuO2, Fe / S L NC exhibits a higher open circuit voltage. Fig.13 The Fe / S prepared in Example 1 L Peak power density test of zinc-air battery with NC catalyst and commercial Pt / C+RuO2, compared with commercial Pt / C, Fe / S L NC exhibits higher peak power density.
[0119] Fig.14 This is a comparison chart of the ORR LSV of the catalysts prepared in Examples 1, 3 and 5 (using L-cysteine as the sulfur source). It can be seen from the figure that the catalyst in Example 1 has the best performance, indicating that when L-cysteine is used as the sulfur source, adding 1.5 mmol L-cysteine is the optimal synthesis condition.
[0120] Fig.15 This is a comparison chart of the ORR LSV of the catalysts prepared in Examples 2, 4 and 6 (using thiourea as the sulfur source). It can be seen from the figure that the catalyst in Example 2 has the best performance, indicating that when thiourea is used as the sulfur source, adding 1.5 mmol thiourea is the optimal synthesis condition.
[0121] Fig.16 This is a comparison chart of ORR LSV of the catalysts prepared in Comparative Examples 1, 3 and 4. As can be seen from the figure, the performance of the catalyst in Comparative Example 1 is the best, indicating that controlling the temperature to 800° C. during the second step of calcination is the optimal synthesis condition.
[0122] In summary, the preparation method of the present invention can accurately control the electronic regulation mode of S atoms on Fe species, breaking the uncertainty of the relationship between traditional doping atoms and Fe species. L In the NC catalyst, S forms Fe-S bonds with Fe species for direct electronic regulation, while Fe / S using thiourea as the sulfur source T In the NC catalyst, S and Fe species are not bonded to perform remote electronic regulation. Both electronic regulation methods can improve the catalytic activity of the catalyst for ORR and OER reactions. Especially when L-cysteine is used as the sulfur source, the direct electronic regulation of S atoms on Fe species changes the electronic structure of the active site, making the catalyst have better electrocatalytic activity and stability for ORR and OER reactions.
[0123] Although the present invention is described above through specific embodiments, it should be understood that any equivalent improvements made by ordinary technicians in this field without departing from the scope of the present invention should be covered by the protection scope of the present invention.
Claims
1. A method for preparing a N and S co-doped Fe-based electrocatalyst, characterized in that The steps include: S1, mixing a sulfur source, a carbon support, dicyandiamide and an iron source uniformly to obtain a mixture precursor; S2, calcining the mixture precursor under an inert atmosphere, first heating the mixture to 500-600° C. and keeping the temperature for 1-3 hours, then heating the mixture to 700-900° C. and keeping the temperature for 1-3 hours, to obtain a N and S co-doped Fe-based electrocatalyst; Wherein, the sulfur source is L-cysteine or thiourea.
2. The preparation method according to claim 1, characterized in that Step S1 includes: S11, mixing the sulfur source, the carbon carrier and dicyandiamide in a predetermined ratio; S12, adding an iron source to the mixture obtained in step S11, and mixing evenly to obtain the mixture precursor.
3. The preparation method according to claim 2, characterized in that: Step S11 uses a grinding method to uniformly mix the sulfur source, the carbon carrier and the dicyandiamide, and ethanol is added as a dispersant during the grinding process.
4. The preparation method according to claim 2, characterized in that: In step S12, ferric nitrate as the iron source is first dissolved in ethanol, and then the ethanol solution of ferric nitrate is added to the mixture obtained in step S11 and ground and mixed.
5. The preparation method according to claim 2, characterized in that: In step S11, the sulfur source, the carbon carrier and dicyandiamide are mixed in a mass ratio of 7 to 25:5:
200.
6. The preparation method according to claim 1, characterized in that: In step S1, the mass ratio of the iron source to the carbon carrier is 1.5-2.5:
5.
7. The preparation method according to claim 1, characterized in that: The carbon carrier is carbon black.
8. The preparation method according to claim 1, characterized in that: In step S2, the temperature is first increased to 550°C at a heating rate of 2°C / min to 3°C / min and kept at this temperature for 2 hours, and then increased to 800°C at a heating rate of 3°C / min to 6°C / min and kept at this temperature for 2 hours.
9. Use of the N, S co-doped Fe-based electrocatalyst obtained according to the preparation method of any one of claims 1 to 8 in OER reaction.
10. Use of the N, S co-doped Fe-based electrocatalyst obtained according to the preparation method of any one of claims 1 to 8 in ORR reaction.